Write y = (x – 6)(x – 4)(x + 2) in standard form.
A.
y = x3 + 48
B.
y = x3 – 8x2 + 4x + 48
C.
y = x3 – 2x2 + 4x – 8
D.
y = x3 – 8x2 – 8x + 24

y = (x – 6)(x – 4)(x + 2) in standard form is y = x^3 – 8x^2 + 4x + 48 (x – 6)(x – 4)(x + 2) = (x^2 - 10x + 24)(x + 2) = x^3 - 8x^2 + 4x + 48

Question

Asked 5/18/2014 10:35:56 AM

Updated 5/18/2014 10:56:01 AM

1 Answer/Comment

Rating

3

y = (x – 6)(x – 4)(x + 2) in standard form is y = x^3 – 8x^2 + 4x + 48

(x – 6)(x – 4)(x + 2) = (x^2 - 10x + 24)(x + 2) = x^3 - 8x^2 + 4x + 48

(x – 6)(x – 4)(x + 2) = (x^2 - 10x + 24)(x + 2) = x^3 - 8x^2 + 4x + 48

Added 5/18/2014 10:56:01 AM

This answer has been confirmed as correct and helpful.

Confirmed by alfred123 [5/18/2014 10:58:06 AM]

The minimum value of a parabola that opens upward will be its vertex.
A.
True
B.
False
**Weegy:** The vertex of a parabola is the point where the parabola crosses its axis. If the coefficient of the x2 term is positive, the vertex will be the lowest point on the graph, the point at the bottom of the ?U?-shape. [ If the coefficient of the x2 term is negative, the vertex will be the highest point on the graph, the point at the top of the ?U?-shape.
The standard equation of a parabola is
y = ax2 + bx + c.
But the equation for a parabola can also be written in "vertex form":
y = a(x ? h)2 + k ] (More)

Question

Updated 5/19/2014 8:47:34 PM

1 Answer/Comment

. Identify the vertex and y-intercept of the graph of f(x) = –3(x + 6)2 + 9.
A.
(–6, –9), y-intercept –99
B.
(6, 9), y-intercept –9
C.
(–6, 9), y-intercept –99
D.
(6, –9), y-intercept –9

Question

Updated 5/19/2014 8:45:48 PM

1 Answer/Comment

Identify the vertex and y-intercept of the graph of f(x) = –4(x + 3)2 + 7.
A.
(3, –7), y-intercept –5
B.
(–3, 7), y-intercept –29
C.
(–3, –7), y-intercept –29
D.
(3, 7), y-intercept –5

Question

Updated 5/19/2014 8:44:22 PM

1 Answer/Comment

The vertex of f(x) = 3(x+2)2 – 4 is (-2,-4).
A.
True
B.
False
**Weegy:** -2.5 + 6.3 + (-4.1) = -0.3 (More)

Question

Updated 5/19/2014 8:06:07 PM

1 Answer/Comment

Factor 4y2 – 9.
A.
(2y + 3)(2y + 3)
B.
(2y - 3)(y - 3)
C.
(y + 3)(2y - 3)
D.
(2y + 3)(2y - 3)
**Weegy:** (4y^2)(2y) = 8y^3 (More)

Question

Updated 5/15/2014 11:26:03 PM

1 Answer/Comment

29,993,937

questions answered

There are no comments.